Early Monitoring and Subsequent Gain of Tacrolimus Time-In-Therapeutic Range May Improve Clinical Outcomes After Living Kidney Transplantation. Issue 6 (December 2021) - Yin, Saifu; Huang, Zhongli; Wang, Zhiling; Fan, Yu; Wang, Xianding; Song, Turun; Lin, Tao
Abstract : Background: The early identification of recipients at high risk of graft loss is clinically relevant after kidney transplantation. The authors explored whether the earlier monitoring of tacrolimus (Tac) time-in-therapeutic range (TTR) is predictive of and a subsequent gain in TTR improves transplant outcomes. Methods: The TTR within 3, 6, 9, and 12 months was evaluated. Multivariate Cox analyses were performed to explore when TTR was predictive of transplant outcomes. Patients were divided into 3 groups based on incremental TTR change [TTR gain (increase >10%), TTR stable (maintained within 10%), and TTR loss (decrease >10%)] and 4 groups based on predefined cutoff values [low–low (LL), low–high (LH), high–low (HL), and high–high (HH)] using 6- and 12-month TTRs. Death-censored graft loss and patient death were primary outcomes. Results: Nonlinear associations were observed between 6-, 9-, and 12-month TTR and death-censored graft and patient survival rates. In multivariate analysis, every 10% increase in 6-, 9-, and 12-month TTRs was associated with reduced patient death [hazard ratio (HR): 0.83; HR: 0.68; HR: 0.61, respectively] and graft loss (HR: 0.88; HR: 0.73; HR: 0.66, respectively). A nonlinear relationship was observed between transplant outcomes and incremental changes in TTR. TTR gain and stable TTR contributed to higher graft survival (HR: 0.20; HR: 0.21) and patient survival (HR: 0.14; HR: 0.15) rates than TTR loss, whereas the former 2 had comparable outcomes. Furthermore, compared with those in the HH group, the LL and HL groups had inferior graft survival (HR: 3.33; HR: 5.17) and patient survival (HR: 5.15; HR: 8.94) rates, whereas the LH group had similar outcomes ( P = 0.63, P = 0.97). Nonadherence was the main controllable risk factor for low TTR. Conclusions: The 6-month TTR identified patients at higher risk of worse outcomes. The subsequent gain of TTR may contribute to better transplant outcomes. Abstract : Supplemental Digital Content is Available in the Text.